A study on the leadership that affect the employee’s motivation at Kapar Energy Ventures Sdn Bhd, Klang Selangor / Norhidayah Omar - Omar, Norhidayah (Faculty of Business and Management, 2009)
This study provides an analysis regarding transformational leadership style which has potential to influence employees’ commitment. The main objective of this project paper is to determine the level of employees’ motivation as well as the level of transformational leadership behavior that been practice at Kapar Energy Ventures Sdn Bhd (Sultan Salahuddin Abdul Aziz Power Station). This research is focusing on employees at Kapar Energy Ventures Sdn Bhd, which consist of 499 staff. The theoretical framework of this study consists of the issues that lead to the motivation of the employees. The main issues will discuss is the leadership style practices at Kapat Energy Ventures Sdn Bhd and organizational culture in term of communication between leadership and employees. Data collections are gathering from the observations and interviews.